PENERAPAN MODEL PEMBELAJARAN KREATIF UNTUK MENINGKATKAN KETERAMPILAN MEMBUAT BENDA KERAJINAN YANG DAPAT DIGERAKKAN OLEH ANGIN UNTUK SISWA KELAS III SDN 05 PEKANBARU. - Safaina, Eka Nurul Safaina Nurul; Antosa, Zairul Antosa Zairul; ', Hj. Lismasila Hj. Lismasila (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The background of thisresearch is still low skills make craft objectsthat can be moved by the wind the third grade students of SDN 05 Pekanbaru. Thepurpose of this research is to improve the skills of making crafts that can be driven bywinds third grade students of SDN 05 Pekanbaru with the application of creativelearning model. This study took place at SDN 05 Pekanbaru. This research is aclassroom action research (PTK). The subjects were students of class III SD Negeri 05Pekanbaru with a total of 26 people consisting of 12 female students and 14 malestudents. Based on the results of research and discussion in mind that the application ofcreative learning model can improve the skills of making crafts that can be driven bythe wind for the third grade students of SDN 05 Pekanbaru. It is known from thestudent's skills before learning to creative learning is only achieved at an average of69.6. In the first cycle or after the implementation of creative learning model, theaverage skills of students increased to 74.94, then rose to 80.06 in the second cycle. Theclassical skills achieved in 26 students (100%). Thus, the hypothesis which says ifimplemented creative learning model, it can increase the skill make craft objects thatcan be moved by the wind the third grade students of SDN 05 Pekanbaru,unacceptable..Keywords: Creative Learning Model, Skills Crafts to Make Objects Driven by Wind